TINGGALAN-TINGGALAN ARKEOLOGIS SARANA MILITER JEPANG MASA PERANG DUNIA II DI SITUS LAPANGAN UDARA AMBESEA KABUPATEN KONAWE SELATAN - hamdan hamado (Laboratorium Jurusan Arkeologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2017)
Ambesea Air Field is a residual military airfield site built by Japan duringWorld War II or the Pacific War. The issues raised in this study were: (1) Whatremains of Japanese military facilities found on the Ambesea Airfield site. (2) Whatis the function of Japanese military facilities at the Ambesea Airfield site. Thisstudy aims to find out the types of relics and functions of the remains of Japanesemilitary facilities found on the AmbeseaAir Field site.This study uses the theory ofwarfare and the theory of battlefield archeology. The results of the study show thatthe remains of Japanese military facilities on the Ambesea Air Field site consist of5 pillar buildings, 4 finding underground tunnels, 2 findings of water tanks, 1 findingrevetments, 2 findings, furnace features 6, 9 ceramic fragments were found and 2glass bottle fragments were found.